Understanding Culinary Tourism Preferences: A Study of Local Food Preferences in Indonesia - Tunjungsari, Hetty Karunia; Buana, Salsabilla Ayundha Martsha; Hoo, Wong Chee; Wolor, Christian Wiradendi (Journal of Applied Data Sciences, 2025)
To encourage the contribution of tourism to grow from time to time, it is necessary to have a driving factor for the success of tourism. The government also relies on the number of visits from domestic tourists in increasing tourism power so it is very important for the government to pay more attention to domestic tourists. This study explores the factors influencing tourist satisfaction in local food culinary tourism sector, identifying key drivers and challenging existing assumptions. There were 242 tourists participated freely to fill online questionnaire in the study. The research highlights the importance of Perceived Quality (PQ), Costs and Risks (CR), and Gastronomy Tourist Market Assessment (GTME) as primary determinants of satisfaction. PQ emphasizes the significance of service quality and authenticity, while GTME underscores the role of market positioning in enhancing the tourist experience. Unexpectedly, CR was found to positively influence satisfaction, suggesting that moderate costs and perceived risks may enhance the appeal of culinary tourism. In contrast, Local Food Satisfaction (LFD), Destination Image (DI), Perceived Value (PV), and Tourist Expectations (TE) exhibited statistical significance but had a less pronounced practical impact on overall satisfaction. These findings contribute to the tourism satisfaction theory by emphasizing the need for context-specific models and offering actionable insights for tourism stakeholders. The study suggests that improving service quality, strategic market positioning, and finding a balance between affordability and perceived adventure can enhance the culinary tourism experience. This study introduces a novel application of tourism satisfaction theory by demonstrating the importance of contextualizing satisfaction models specifically for culinary tourism—an area often overlooked in broader tourism satisfaction research.